Preparation method of heterogeneous metal loaded carbon nano box
The preparation of heterogeneous metal-supported carbon nanoboxes was solved by a one-step low-temperature calcination method, and the problems of structural complexity and upper limit of catalytic activity in the prior art were solved, and the symbiotic loading of single atoms and atom clusters was achieved, thereby improving the electrocatalytic performance.
Patent Information
- Application Number
- CN202411083562.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the nanostructures of metal-loaded metals lack structural complexity and cannot effectively regulate the reaction intermediates. A single metal site cannot independently regulate catalytic activity and selectivity, resulting in a low upper limit of catalytic activity and difficulty in optimizing bifunctional catalysis.
A one-step low-temperature calcination method is used to prepare heterogeneous metal-supported carbon nanoboxes. By uniformly dispersing the mixture of transition metal salts in deionized water, adding functional carbon nanoboxes to freeze drying and low-temperature calcination, the symbiosis of single atoms and atom clusters is achieved. Load, suitable for all transition family metal elements.
The companion symbiosis between single atoms and atomic clusters is achieved, the electrocatalytic performance of HER is improved, and theoretically applicable to all transition group metal elements, significantly improving catalytic activity and selectivity.
Smart Images

Figure CN119121312A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon nano box, in particular to a method for preparing a heterogeneous metal-loaded carbon nano box. Background Art
[0002] Currently, metal-loaded nanostructures are the most widely used type of heterogeneous catalysts. However, due to the lack of structural complexity, they are not suitable for complex reactions and cannot regulate the adsorbed intermediates during the reaction. Secondly, a single metal species site cannot independently regulate the catalytic activity and selectivity of different pathways, resulting in a low upper limit of catalytic activity. In addition, a single metal site is very difficult to optimize the simultaneous dual-functional catalysis.
[0003] Atomically precise catalysts with single-atom, diatomic, and polyatomic cluster species are an emerging class of heterogeneous catalysts that exhibit high atomic utilization due to atomic dispersion and minimize the use of precious metals. Electrocatalysts based on atomically precise composite sites have attracted great attention in recent years. Composite sites include dual or multiple types of atomically precise metal species, such as heterogeneous diatomic sites, heterogeneous atomic cluster sites, single-atom-atom cluster composite sites, and single-atom-nanoparticle composite sites. Compared with conventional single metal sites, composite sites provide significantly enhanced catalytic performance due to the intrinsic synergistic effect generated by the interaction of adjacent heterogeneous metal species.
[0004] However, the development of atomically precise composite site catalysts is still in its early stages, mainly due to the complex catalyst synthesis. Usually, a metal species-by-metal synthesis process and multi-step reactions are required to construct composite sites, which is not only time-consuming and labor-intensive, but also has little universality for different metal elements. Due to the very limited diversity of composite configurations, in-depth studies of structure-activity relationships are also greatly restricted.
[0005] Other methods known so far all use multi-step preparation, and other methods known so far do not have element universality. Summary of the invention
[0006] The present invention provides a method for preparing heterogeneous metal-loaded carbon nanoboxes, which solves the problem that the existing methods all use multiple steps for preparation and have no element universality. The present invention uses a one-step low-temperature calcination method, which is theoretically universally applicable to all transition metal elements.
[0007] A method for preparing a heterogeneous metal-loaded carbon nanobox is achieved by the following one-pot process: a mixture of transition metal salts is uniformly dispersed in deionized water, a functional carbon nanobox is added, and the mixture is stirred evenly and freeze-dried to obtain a precursor; the precursor is low-temperature calcined in an argon atmosphere to obtain a heterogeneous metal-loaded carbon nanobox; wherein at least one transition metal is loaded in the form of a single atom, and at least another transition metal is loaded in the form of an atomic cluster; The functional carbon nanobox is a carbon nanobox having functional groups on its surface; The mixture of transition metal salts contains at least two metal salts of transition metals; the transition metal salts are chlorides, nitrates, acetates or acetylacetonates; The heating rate of low-temperature calcination is 5-10°C / min, the calcination temperature is 350-650°C, and the holding time after reaching the temperature is 1-3h.
[0008] Furthermore, the transition metal is selected from titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, palladium, tungsten, iridium or platinum.
[0009] Furthermore, the molar ratio of the transition metal supported in the form of single atoms to the transition metal supported in the form of atomic clusters is 1:(0.5~2).
[0010] Furthermore, the ratio of the transition metal to deionized water and the functional carbon nanobox is 0.03-0.07 mmol:10 mL:10-20 mg.
[0011] Furthermore, the preparation process of the functional carbon nanobox is as follows: using metal salt as a template precursor under the protection of inert gas, chemical vapor deposition is performed using an organic solvent; the deposited solid is acid-washed and dried to obtain the functional carbon nanobox. As is common knowledge in the art, chemical vapor deposition requires high temperature, so a corresponding metal salt with high temperature stability will be selected.
[0012] Furthermore, the metal salt template precursor is basic magnesium carbonate, calcium oxide or iron oxide. Furthermore, the organic solvent is acetonitrile, thiophene or acetone.
[0013] Furthermore, the pickling temperature is 25-80°C, and the pickling time is 12-24h.
[0014] Furthermore, the heating rate of chemical vapor deposition is 5-10°C / min, the chemical vapor deposition temperature is 800-950°C, and the insulation time after reaching the temperature is 1-3h.
[0015] The beneficial effects of the present invention are: (1) Single atoms and atomic clusters coexist through a one-step low-temperature calcination method; (2) Theoretically, it is applicable to all transition metal elements, and experimental evidence includes more than a dozen transition elements; (3) Due to the coexistence of single atoms and atomic clusters, strong electronic interactions are generated, which greatly improves the HER electrocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox. The iron single atom and ruthenium atom cluster coexistence composite site catalyst (Fe SA Ru AC @NCB) Transmission electron microscopy (a) bright field image; (b) dark field image; (c) element distribution map of Ru; (d) element distribution map of Fe; (e) line scan illustration; (f) line scan maps of Ru and Fe; Figure 2 The Fe prepared in Example 1 of the method for preparing a heterogeneous metal-loaded carbon nanobox of the present invention is SA Ru AC @LSV curves of hydrogen evolution of NCB catalyst and Pt / C in 1 M KOH electrolyte; Figure 3 The cobalt single atom and ruthenium atom cluster coexistence composite site catalyst (Co SA Ru AC @SCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Co; Figure 4 The cobalt single atom and ruthenium atom cluster coexistence composite site catalyst (Ni SA Ru AC @OCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Ni; Figure 5 The titanium single atom and ruthenium atom cluster coexistence composite site catalyst (Ti SA Ru AC @NCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Ti; Figure 6 The chromium single atom and ruthenium atom cluster coexistence composite site catalyst (Cr SA Ru AC@NCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Cr; Figure 7 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox, and the prepared manganese single atom and ruthenium atom cluster coexistence composite site catalyst (Mn SA Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Mn; Figure 8 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox, and the copper single atom and ruthenium atom cluster coexistence composite site catalyst (Cu SA Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Cu; Fig. 9 The zinc single atom and ruthenium atom cluster coexistence composite site catalyst (Zn SA Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Zn; Fig.10 The palladium single atom and ruthenium atom cluster coexistence composite site catalyst (Pd SA Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ru; (c) element distribution map of Pd; Fig.11 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox in Example 10, wherein the iron single atom and tungsten atom cluster coexisting composite site catalyst (Fe SA W AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Fe; (c) element distribution map of W; Fig.12 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox in Example 11, wherein the cobalt single atom and molybdenum atom cluster coexisting composite site catalyst (Co SA Mo AC @NCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Co; (c) element distribution map of Mo; Fig.13The nickel single atom and vanadium atom cluster coexistence composite site catalyst (Ni SA V AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ni; (c) element distribution map of V; Fig.14 The titanium single atom and rhodium atom cluster coexistence composite site catalyst (Ti) prepared in Example 13 of the method for preparing a heterogeneous metal-supported carbon nanobox of the present invention SA R AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution map of Ti; (c) element distribution map of Rh; Fig.15 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox, and the chromium single atom and iridium atom cluster coexistence composite site catalyst (Cr SA Ir AC @NCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Cr; (c) element distribution map of Ir; Fig.16 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox, and the iron, cobalt single atom and ruthenium atom cluster coexistence composite site catalyst (Fe SA Co SA Ru AC @NCB) Transmission electron microscope (a) dark field image; (b) element distribution map of Fe; (c) element distribution map of Co; (d) element distribution map of Ru; Fig.17 The present invention is a method for preparing a heterogeneous metal-supported carbon nanobox, and the iron, cobalt single atom and ruthenium atom cluster coexistence composite site catalyst (Fe SA Co SA Ru AC @NCB) (a) Line scan illustration; (b) Line scan images of Ru, Fe and Co; Fig.18 The present invention is a method for preparing a heterogeneous metal-loaded carbon nanobox in Example 16, wherein the single atoms of iron, cobalt, and nickel and the clusters of ruthenium and platinum atoms coexist in a composite site catalyst (Fe SA Co SA Ni SA Pt AC Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution of Fe; (c) element distribution of Co; (d) element distribution of Ni; (e) element distribution of Ru; (f) element distribution of Pt; Fig.19The present invention is a method for preparing a heterogeneous metal-loaded carbon nanobox in Example 16, wherein the single atoms of iron, cobalt, and nickel and the clusters of ruthenium and platinum atoms coexist in a composite site catalyst (Fe SA Co SA Ni SA Pt AC Ru AC @NCB) (a) Line scan illustration; (b) Line scan results of Ru, Pt, Fe, Co and Ni; Fig. 20 The present invention is a method for preparing a heterogeneous metal-loaded carbon nanobox in Example 17, wherein the single atoms of iron, cobalt, nickel, chromium, manganese and clusters of ruthenium and platinum atoms coexist in a composite site catalyst (Fe SA Co SA Ni SA Cr SA Mn SA Pt AC Ru AC @NCB) Transmission electron microscopy (a) dark field image; (b) element distribution of Fe; (c) element distribution of Co; (d) element distribution of Ni; (e) element distribution of Cr; (f) element distribution of Mn; (g) element distribution of Ru; (h) element distribution of Pt; Fig.21 The present invention is a method for preparing a heterogeneous metal-loaded carbon nanobox in Example 17, wherein the single atoms of iron, cobalt, nickel, chromium, manganese and clusters of ruthenium and platinum atoms coexist in a composite site catalyst (Fe SA Co SA Ni SA Cr SA Mn SA Pt AC Ru AC @NCB) (a) Line scan illustration; (b) Line scan results of Ru, Pt, Fe, Co, Ni, Cr and Mn; Fig. 22 Example 1 of the method for preparing a heterogeneous metal-loaded carbon nanotube of the present invention: Fe SA Ru AC @NCB catalyst and Ru AC @NCB and Fe SA @NCB LSV curve of hydrogen evolution in 1 M KOH electrolyte. DETAILED DESCRIPTION
[0017] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0018] A method for preparing a heterogeneous metal-loaded carbon nanobox is achieved by the following one-pot process: a mixture of transition metal salts is uniformly dispersed in deionized water, a functional carbon nanobox is added, and the mixture is stirred evenly and freeze-dried to obtain a precursor; the precursor is low-temperature calcined in an argon atmosphere to obtain a heterogeneous metal-loaded carbon nanobox; wherein at least one transition metal is loaded in the form of a single atom, and at least another transition metal is loaded in the form of an atomic cluster; The functional carbon nanobox is a carbon nanobox having functional groups on its surface; The mixture of transition metal salts contains at least two metal salts of transition metals; the transition metal salts are chlorides, nitrates, acetates or acetylacetonates; The heating rate of low-temperature calcination is 5-10°C / min, the calcination temperature is 350-650°C, and the holding time after reaching the temperature is 1-3h.
[0019] Furthermore, the transition metal is selected from titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, palladium, tungsten, iridium or platinum.
[0020] Furthermore, when two transition metal salts are used, the molar ratio of the two transition metal salts is (0.5~2):1.
[0021] Furthermore, the preparation process of the functional carbon nanobox is as follows: using metal salt as a template precursor under the protection of inert gas, chemical vapor deposition is performed using an organic solvent; the deposited solid is acid-washed and dried to obtain the functional carbon nanobox. As is common knowledge in the art, chemical vapor deposition requires high temperature, so a corresponding metal salt with high temperature stability will be selected.
[0022] Furthermore, the metal salt template precursor is basic magnesium carbonate, calcium oxide or iron oxide. Furthermore, the organic solvent is acetonitrile, thiophene or acetone.
[0023] Furthermore, the pickling temperature is 25-80°C, and the pickling time is 12-24h.
[0024] Furthermore, the heating rate of chemical vapor deposition is 5-10°C / min, the chemical vapor deposition temperature is 800-950°C, and the insulation time after reaching the temperature is 1-3h.
[0025] The heterogeneous metal-loaded carbon nanobox is a heterogeneous transition metal composite site carbon-based catalyst. The heterogeneous metals undergo different sintering kinetics, and after pyrolysis, metal atom clusters and single atoms are realized as composite site catalysts. The existence state of the active sites of the heterogeneous metal-loaded carbon nanobox can be regulated by changing the type of metal salt used in the preparation process.
[0026] Example 1 Under the protection of inert gas, basic magnesium carbonate was used as a precursor, and a gas washing bottle containing acetonitrile was placed upstream of the tube furnace gas path. Chemical vapor deposition was performed at a heating rate of 5°C / min, and the temperature was raised to 900°C and kept for 3 hours. After the deposition, the solid was acid-washed and dried to obtain a black powder, which was the nitrogen-doped carbon nanobox;
[0027] 0.01mmol of ferric chloride hexahydrate and 0.02mmol of ruthenium chloride were evenly dispersed in 10mL of deionized water and ultrasonicated for 10 minutes. Then 20mg of nitrogen-doped carbon nanoboxes were added and stirred at 25°C for 24h. After the metal salt and nitrogen-doped carbon nanoboxes were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst with coexistence of iron single atoms and ruthenium atomic clusters, labeled as Fe SA Ru AC @NCB.
[0028] For the Fe of Example 1 SA Ru AC @NCB catalyst was observed by transmission electron microscopy. Figure 1 It can be seen that there are obvious metal clusters. The EDS elemental analysis and line scan shown in the figure further confirm the distribution of iron and ruthenium elements on the nitrogen-doped carbon nanobox. Under the same synthesis conditions, the distribution form of iron sites is metal single atoms, and the ruthenium sites are effectively dispersed in the form of atomic clusters. The synthesis strategy can effectively regulate the distribution form of active sites of heterogeneous metals.
[0029] For the Fe of Example 1 SA Ru AC @NCB catalyst was electrochemically tested, and the results are as follows Figure 2 As shown in the LSV curve, it can be seen that the prepared Fe SA Ru AC @NCB catalyst has excellent performance, far exceeding commercial Pt / C catalyst.
[0030] Example 2 Under the protection of inert gas, basic magnesium carbonate was used as a precursor, and a washing bottle containing thiophene was placed upstream of the tube furnace gas path. Chemical vapor deposition was performed at a heating rate of 5°C / min, and the temperature was raised to 900°C and kept for 2 hours. After the deposition, the solid was acid-washed and dried to obtain a black powder, which was the sulfur-doped carbon nanobox;
[0031] 0.01mmol of cobalt chloride hexahydrate and 0.02mmol of ruthenium chloride were evenly dispersed in 10mL of deionized water and ultrasonicated for 10 minutes. Then 20mg of sulfur-doped carbon nanobox was added and stirred at 25°C for 24h. After the metal salt and sulfur-doped carbon nanobox were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst with coexistence of cobalt single atoms and ruthenium atomic clusters, labeled as Co SA Ru AC @SCB.
[0032] For Co of Example 2 SA Ru AC @SCB catalyst was observed by transmission electron microscopy and EDS elemental analysis. Figure 3 It can be seen that there are obvious metal clusters. The distribution form of cobalt sites is metal single atoms, and the ruthenium sites are effectively dispersed in the form of atomic clusters.
[0033] Example 3 Under the protection of inert gas, calcium oxide was used as a precursor, and a washing bottle containing acetone was placed upstream of the tube furnace gas path. Chemical vapor deposition was performed at a heating rate of 2°C / min, and the temperature was raised to 850°C and kept for 3 hours. After the deposition, the solid was acid-washed and dried to obtain a black powder, which was the oxygen-doped carbon nanobox;
[0034] 0.01mmol nickel chloride hexahydrate and 0.02mmol ruthenium chloride were evenly dispersed in 10mL deionized water and ultrasonicated for 10 minutes. Then 20mg oxygen-doped carbon nanobox was added and stirred at 25°C for 24h. After the metal salt and oxygen-doped carbon nanobox were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst with coexistence of nickel single atoms and ruthenium atomic clusters, labeled as Ni SA Ru AC @OCB.
[0035] For Ni in Example 3 SA Ru AC @OCB catalyst was observed by transmission electron microscopy and EDS elemental analysis. Figure 4 It can be seen that there are obvious metal clusters. The distribution form of nickel sites is metal single atoms, and the ruthenium sites are effectively dispersed in the form of atomic clusters.
[0036] Example 4 Compared with Example 1, the type of transition metal salt was changed, and ferric chloride hexahydrate was changed to bis(acetylacetonate)diisopropoxide titanium. The remaining steps were the same to prepare a composite site catalyst (labeled as Ti SA Ru AC @NCB).
[0037] For Ti of Example 4 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Figure 5 shown.
[0038] Embodiment 5: Compared with Example 1, the type of transition metal salt was changed to chromium acetylacetonate instead of ferric chloride hexahydrate, and the remaining steps were the same to prepare a composite site catalyst in which chromium single atoms and ruthenium atomic clusters coexisted (labeled as Cr SA Ru AC @NCB).
[0039] For Cr in Example 5 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Figure 6 shown.
[0040] Embodiment 6: Compared with Example 1, the type of transition metal salt was changed to manganese acetylacetonate instead of ferric chloride hexahydrate, and the remaining steps were the same to prepare a composite site catalyst in which manganese single atoms and ruthenium atomic clusters coexisted (labeled as Mn SA Ru AC @NCB).
[0041] For Mn in Example 6 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Figure 7 shown.
[0042] Embodiment 7: Compared with Example 1, the type of transition metal salt was changed, and ferric chloride hexahydrate was changed to copper chloride dihydrate. The remaining steps were the same to prepare a composite site catalyst in which copper single atoms and ruthenium atomic clusters coexisted (labeled as Cu SA Ru AC @NCB).
[0043] For the Cu of Example 7 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Figure 8 shown.
[0044] Embodiment 8: Compared with Example 1, the type of transition metal salt was changed to zinc chloride instead of ferric chloride hexahydrate, and the remaining steps were the same to prepare a composite site catalyst in which single zinc atoms and ruthenium atomic clusters coexisted (labeled as Zn SA Ru AC @NCB).
[0045] For Zn in Example 8 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig. 9 shown.
[0046] Embodiment 9: Compared with Example 1, the type of transition metal salt was changed to palladium chloride instead of ferric chloride hexahydrate, and the remaining steps were the same to prepare a composite site catalyst (labeled as Pd SA Ru AC @NCB).
[0047] For Pd in Example 9 SA Ru AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.10 shown.
[0048] Embodiment 10: Compared with Example 1, the type of transition metal salt was changed, ruthenium chloride was changed to tungsten chloride, and the remaining steps were the same to prepare a composite site catalyst (labeled as Fe SA W AC @NCB).
[0049] For Fe in Example 10 SA W AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.11 shown.
[0050] Embodiment 11: Compared with Example 1, the type of transition metal salt was changed, ferric chloride hexahydrate was changed to cobalt chloride hexahydrate, ruthenium chloride was changed to molybdenum acetylacetonate, and the remaining steps were the same to prepare a composite site catalyst in which cobalt single atoms and molybdenum atomic clusters coexisted (labeled as Co SA Mo AC @NCB).
[0051] For Co of Example 11 SA Mo AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.12 shown.
[0052] Embodiment 12: Compared with Example 1, the type of transition metal salt was changed, ferric chloride hexahydrate was changed to nickel chloride hexahydrate, ruthenium chloride was changed to vanadium acetylacetonate, and the other steps were the same to prepare a composite site catalyst in which nickel single atoms and vanadium atomic clusters coexisted (labeled as Ni SA V AC @NCB).
[0053] For Ni in Example 12 SA V AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.13 shown.
[0054] Embodiment 13: Compared with Example 1, the type of transition metal salt was changed, ferric chloride hexahydrate was changed to bis(acetylacetonate)diisopropoxide titanium, ruthenium chloride was changed to rhodium trichloride, and the other steps were the same to prepare a composite site catalyst (labeled as Ti SA R AC @NCB).
[0055] For Ti of Example 13 SA R AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.14 shown.
[0056] Embodiment 14: Compared with Example 1, the type of transition metal salt was changed, ferric chloride hexahydrate was changed to chromium acetylacetonate, ruthenium chloride was changed to iridium chloride, and the other steps were the same to prepare a composite site catalyst in which chromium single atoms and iridium atomic clusters coexisted (labeled as Cr SA Ir AC @NCB).
[0057] For Cr in Example 14 SA Ir AC @NCB catalyst was characterized by transmission electron microscopy and element distribution test. The results are as follows Fig.15 shown.
[0058] Embodiment 15 The nitrogen-doped carbon nanotubes were prepared by the same method as in Example 1; 0.01mmol ferric chloride hexahydrate, 0.01mmol cobalt chloride hexahydrate and 0.01mmol ruthenium chloride were uniformly dispersed in 10mL deionized water and ultrasonicated for 10 minutes. Then 10mg nitrogen-doped carbon nanobox was added and stirred at 25°C for 24h. After the metal salt and nitrogen-doped carbon nanobox were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst in which single atoms of iron, cobalt and ruthenium atoms coexisted, labeled as Fe SA Co SA Ru AC @NCB.
[0059] For Fe in Example 15 SA Co SA Ru AC @NCB catalyst was characterized by transmission electron microscopy, element distribution test and line scan test. The results are as follows Fig.16 , 17 shown.
[0060] Example 16 The nitrogen-doped carbon nanotubes were prepared by the same method as in Example 1; 0.01mmol ferric chloride hexahydrate, 0.01mmol cobalt chloride hexahydrate, 0.01mmol nickel chloride hexahydrate, 0.01mmol chloroplatinic acid hexahydrate and 0.01mmol ruthenium chloride were uniformly dispersed in 10mL deionized water and ultrasonicated for 10 minutes. Then 10mg nitrogen-doped carbon nanobox was added and stirred at 25°C for 24h. After the metal salt and nitrogen-doped carbon nanobox were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst in which single atoms of iron, cobalt, and nickel coexisted with clusters of platinum and ruthenium atoms, labeled as Fe SA Co SA Ni SA Pt AC Ru AC @NCB.
[0061] For Fe in Example 16 SA Co SA Ni SA Pt AC Ru AC @NCB catalyst was characterized by transmission electron microscopy, element distribution test and line scan test. The results are as follows Fig.18 , 19 shown.
[0062] Embodiment 17 The nitrogen-doped carbon nanotubes were prepared by the same method as in Example 1; 0.01mmol ferric chloride hexahydrate, 0.01mmol cobalt chloride hexahydrate, 0.01mmol nickel chloride hexahydrate, 0.01mmol chromium acetylacetonate, 0.01mmol manganese acetylacetonate, 0.01mmol chloroplatinic acid hexahydrate and 0.01mmol ruthenium chloride were uniformly dispersed in 10mL deionized water and ultrasonicated for 10 minutes. Then 10mg nitrogen-doped carbon nanobox was added and stirred at 25°C for 24h. After the metal salt and nitrogen-doped carbon nanobox were evenly dispersed, freeze-dried to obtain a precursor. In an argon atmosphere with a flow rate of 60mL / min, the temperature was raised to 500°C at a rate of 10°C / min, kept warm for 1h, and then naturally cooled to room temperature to obtain a composite site catalyst in which single atoms of iron, cobalt, nickel, chromium, and manganese and clusters of platinum and ruthenium atoms coexisted, marked as Fe SA Co SA Ni SA Cr SA Mn SA Pt AC Ru AC @NCB.
[0063] For Fe in Example 17 SA Co SA Ni SA Cr SA Mn SA Pt AC Ru AC @NCB catalyst was characterized by transmission electron microscopy, element distribution test and line scan test. The results are as follows Fig. 20 , 21 shown.
[0064] In this patent, heterogeneous metal composite sites are achieved through a one-step low-temperature sintering method. During the sintering process, metal species with different atomic structures are generated simultaneously in time and adjacent to each other in space. From the perspective of chemical principles, the driving force for metal sintering is cohesive energy. At the same time, isolated metal atoms also need to overcome the binding energy and diffusion energy barriers on the carbon nanobox matrix, and finally sinter to form clusters. Relying on this characteristic, by designing the types and structures of functional groups and metal salts on the surface of the carbon nanobox, the regulation of metal binding energy and diffusion energy is achieved. Therefore, driven by the difference in cohesive energy of different metals, different metals can be simultaneously changed into different atomic combinations on the functional carbon nanobox during the sintering process, thereby achieving the symbiosis of multiple metal species and producing native interactions.
[0065] Symbiosis manifests itself in the form of simultaneous generation in time and adjacent generation in space. Specifically, first, the two metal cations are fully impregnated with the functional carbon nanobox. Due to the strong complexation of the polar groups on the functional carbon nanobox with the metal cations, the cations tend to disperse near the heterogeneous functional groups. As the temperature increases, the metal elements with higher cohesive energy overcome the energy barriers of binding and diffusion and gradually sinter the performance clusters; the metal elements with low cohesive energy cannot drive their sintering, but establish strong metal-matrix interactions with the functional carbon nanobox to form single-atom sites. Therefore, specific composite sites can be effectively constructed on the functional carbon nanobox to form single-atom-atom cluster sites. This method can be easily extended to other bimetallic pairs or multimetal systems.
[0066] The composite site catalysis of metal species constructed by conventional multi-step methods may lack obvious interactions between species, resulting in a weak synergistic effect on electrocatalysis. The atomically precise composite site catalysts obtained by symbiosis can exert a synergistic effect during the synthesis and catalysis process, and different metal sites promote each other to enhance catalytic activity and selectivity. This synergistic effect can be achieved by enhancing the stability of reaction intermediates, promoting the adsorption of reactant molecules, and providing a variety of catalytic active sites. On the other hand, different metals can interact with each other through electronic effects during synthesis, optimize the electronic structure of active sites, enhance metal-substrate interactions, and ultimately improve the activity and selectivity of the catalyst. Finally, the symbiosis of different metals in synthesis can form a more complex coordination environment and provide a variety of catalytic active sites, thereby improving the activity and selectivity of the catalyst. Experimental results also confirm this conclusion, such as Fig. 22 As shown, both the Fe single atom site and the pure Ru cluster site exhibit much worse HER activity than the catalyst with the coexistence of Fe single atoms and Ru atomic clusters, indicating a synergistic mechanism of the composite site in improving the electrocatalytic performance.
[0067] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a heterogeneous metal-loaded carbon nanotube, characterized in that: The method is achieved by the following one-pot method: a mixture of transition metal salts is uniformly dispersed in deionized water, a functional carbon nanobox is added, the mixture is stirred evenly, and then freeze-dried to obtain a precursor; the precursor is low-temperature calcined in an argon atmosphere to obtain a heterogeneous metal-loaded carbon nanobox; wherein at least one transition metal is loaded in the form of a single atom, and at least another transition metal is loaded in the form of an atomic cluster; The functional carbon nanobox is a carbon nanobox having functional groups on its surface; The mixture of transition metal salts contains at least two metal salts of transition metals; the transition metal salts are chlorides, nitrates, acetates or acetylacetonates; The heating rate of low-temperature calcination is 5-10°C / min, the calcination temperature is 350-650°C, and the holding time after reaching the temperature is 1-3h.
2. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 1, characterized in that: The transition metal is selected from titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, palladium, tungsten, iridium or platinum.
3. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 1, characterized in that: The molar ratio of the transition metal supported in the form of single atoms to the transition metal supported in the form of atomic clusters is 1:(0.5~2).
4. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 1, characterized in that: The usage ratio of transition metal, deionized water and functional carbon nanobox is 0.03-0.07mmol:10mL:10-20mg.
5. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 1, characterized in that: The preparation process of the functional carbon nanobox is as follows: metal salt is used as a template precursor under the protection of inert gas, and organic solvent is used for chemical vapor deposition; the deposited solid is acid-washed and dried to obtain the functional carbon nanobox.
6. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 5, characterized in that: The metal salt template precursor is basic magnesium carbonate, calcium oxide or iron oxide.
7. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 5, characterized in that: The organic solvent is acetonitrile, thiophene or acetone.
8. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 5, characterized in that: The pickling temperature is 25~80℃ and the pickling time is 12~24h.
9. The method for preparing a heterogeneous metal-loaded carbon nanobox according to claim 5, characterized in that: The heating rate of chemical vapor deposition is 5-10°C / min, the chemical vapor deposition temperature is 800-950°C, and the insulation time after reaching the temperature is 1-3h.
